Optimization approach for bioethanol production from agro-industrial waste - Murillo-Alvarado, Pascual Eduardo; Flores Russell, Ernesto (Frontiers in Energy Research, 2022)
Currently, the trend is towards seeking energy alternatives that are friendly to the environment without compromising the growth of today's society. Biofuels from biomass processing are the promising path towards the development of a biomass industry and the early replacement of fossil fuels. In this sense, the purpose of this work is to determine the feasibility of generating biofuels through the use of agro-industrial waste through a mathematical model for the optimization of the supply chain for the production of biofuels from waste generated by the food processors in the Municipality of Zamora, Mich. The case study considers the available raw material, which is the waste from the food industries, the period of time in which these are available, as well as the possible places for processing and obtaining biofuels. The results obtained establish that it is possible to obtain 7.27x107 Lt/year of bioethanol through the processing of 3.27x106 ton/year of organic waste, which generates a profit of 4.37x107 USD/year.